REAL OPTIONS I N THE E VALUATION AND RISK MANAGEMENT IN PUBLIC INVESTMENT PROJECTS: CASE MEXICO - Martínez Miranda, Elio (2014)
From the social viewpoint the evaluation of projects in this article presents the way how you could use the methodology of real choices in public investment projects, and proposes the social option of deferring a project applied to a case of extension of a highway bypass in Tepic, Nayarit - Mexico.